(302) Some Problems In Educational Planning in The Arab World. بعض المشاكل في التخطيط التربوي في العالم العربي. - El-Koussy, A. (The Institute Of National Planning., 2018)
Through enthusiasm there was advancement of education in the Arab world during the last 10 or 12 years, but such advancement didn't coincide with needs and was more out of proportion in some sections than in others.